Characterization of two neutralizing monoclonal antibodies with conformational epitopes against porcine deltacoronavirus - Wan Lu; Hongtao Cao; Yongle Yang; Yangyang Sun; Dong Yang; Priscilla F. Gerber; Xiangdong Li; Yaowei Huang; Bin Wang (Animal Diseases)
Abstract Porcine deltacoronavirus (PDCoV) is a globally distributed swine enteropathogenic virus that emerged in the last decade. A recent report of PDCoV infection in Haitian children also highlights potential public health implications. In this study, two monoclonal antibodies (mAbs), 1C2 and 5H5, were generated and showed high specificity for the PDCoV S protein. Both mAbs displayed high-titer neutralizing capabilities, suggesting their potential for passive immunotherapy. Epitope mapping revealed that the mAbs likely recognized conformational epitopes in the S1 subunit domains A and B of the native S protein, thereby blocking the interaction between the S1 receptor-binding domain and the cellular receptor, which could inhibit viral entry into host cells. This study offers new biological tools for PDCoV detection and lays the groundwork for the future development of porcine-specific antibodies for the prevention and treatment of PDCoV in piglets.